Some studies of the reaction between stannic chloride and silver perchlorate in anhydrous media - Peisach, Max (Department of Chemistry, 2016)
The theory of the chemical bond, particularly in compounds where the bonds are neither purely electrovalent nor purely covalent, has in recent years received a great deal of attention. Of the oxy-acids which can form ionic as well as covalent compounds, perchloric acid and sulphuric acid are of special interest because of the electronic symmetry and the stability of their anions, While compounds of the elements of group IV, in the divalent state, are known to be ionic, the exact nature of the bonds formed by these elements in the tetravalent state in their oxy-salts has as yet not been ascertained. It would, therefore, be of interest to review the perchlorates and sulphates of that group.